Insights into the alpaca skin transcriptome in relation to fibre colour - Cransberg, Rhys (Curtin University, 2017)
Through a combination of chemical and genomic data this study has demonstrated that "brown" alpacas are predominantly pheomelanic, and are similar to bay horses in colour phenotype. RNAseq was used to analyse colour genes the alpaca skin-transcriptome, and has provided the first annotation of the alpaca (vicPac2) genome which is not based on in-silico gene-prediction. Upregulated expression of the agouti gene results in white and diluted colour phenotypes in alpacas.